The death of an heir: Adolph Coors III (St. Martin's Press, 2017)
In the 1950s and 60s, the Coors dynasty reigned over Golden, Colorado, seemingly invincible. When rumblings about labor unions threatened to destabilize the family's brewery, Adolph Coors, Jr., the septuagenarian president of the company, drew a hard line, refusing to budge. They had worked hard for what they had, and no one had a right to take it from them.

Wild Horses DVD (State of the Union, 2015)
exas Ranger Samantha Payne reopens a 15-year-old missing person case, and uncovers evidence that suggests that the boy was likely murdered on a ranch belonging to wealthy family man, Scott Briggs. When Scott s estranged son unexpectedly returns home during the investigation, Samantha becomes even more convinced that the Briggs family was involved, and will stop at nothing to discover the truth about the boy s death - even putting her own life in jeopardy.

Flawless (CD) (New York Confidential, 1, 1, 2016)
There's a pub in New York City that's been in the Finnegan family for generations. Now Kieran and her three brothers own it. Kieran Finnegan is also, as it happens, a criminal psychologist-a fitting reaction, perhaps, to her less-than-lawful teenage past.

The Asphalt warrior (Asphalt warrior novels, 1, 1, 2012)
Introducing Denverite Brendan Murphyor Murph as he s known to the rest of the world. He lives alone in his crow s nest apartment, fries a hamburger for every meal, does his dish, then channel surfs for reruns of Gilligans Island. He is a radical minimalist. He strives to earn no more money as a driver for Rocky Mountain Taxi Company than his needs require.